Dvieļu nosaukumu semantika, cilme un areālā izplatība - Jansone, Ilga (Baltistica, 1997)
SEMANTICS, ETYMOLOGY AND LINGUOGEOGRAPHY OF TOWEL NOMINATIONSThe article deals with towel nominations found in vernaculars of the Latvian language. The nominations derived from the root slauk- (found compactly in Southwest Kurzeme, sporadically also in Vidzeme) are considered to be the oldest. A nomination dvielis borrowed from the Old German has taken up a stable place in the Latvian literary language, and in Vidzeme, Kurzeme and Zemgale. The nomination skā(r)teris has been recorded with limited semantics in Bārta (for describing magnificent, ornamented linen used as a towel).Different nominations are found in Latgale. There the most well-known nomination, rich in variants is ručņiks loaned from the Slavonic languages (some of the variants are likely to have been loaned but some of them formed as hybrid forms with the dialect form rūka of a word ruoka in the root). A towel nomination abrūss, etymology of which is being found in the Slavonic languages, still borrowed from the Lithuanian language into the vernaculars of Latvian, is found in the South Latgale, Southwest Latgale and Eastern Zemgale. A towel nomination mutinieks has been recorded in a Latgalian subdialect in Stirniene.
Keywords: latvių kalba; leksika; rankšluosčių pavadinimai